(untitled) (The Chittagong University Journal of Science, 2022)
Wheeler-De Witt (WDW) equation is the central equation of canonical quantum gravity. For its infinite dimensionality to get a meaningful solution of that equation is very hard. To extract minimal information, one has to consider WDW equation in Minisuperspace where there are only two variables, such as known radius of the Universe and the scalar field. In this paper we find the general solution of WDW equation in Minisuperspace. We discuss the physical significance of our solution. The Chittagong Univ. J. Sci. 43(1): 67-74, 2021